CODE MIXING AS A FORM OF INDONESIAN IDENTITY BASED ON THE MOTTO OF BHINNEKA TUNGGAL IKA - Nugraha, Fajar Muhammad (International Review of Humanities Studies, 2019)
In 2018, the Language Comission of the Ministry of Education and Culture (Kemendikbud) of the Republic of Indonesia has made verification towards all the languages that exists in Indonesia. The verification conducted from 1991 to 2017 resulted in 652 languages to be found. That number still does not include the dialects and their sub-divisions of the 652 languages. Meanwhile, UNESCO recorded 143 languages based on their vitality status. Identity can be interpreted as similarity or unity with others in a certain area or other things (Rummens, 1993: 157-159). "The identity possessed by an individual can be in the form of personal identity and social identity" (Santoso, 2006: 44-45). Using statistical data on language issued by the Indonesian Central Bureau of Statistics as a corpus and literature study by tracing the title of mainstream online media coverage related to the use of code mixing, identity theory, and the concept of intercultural communication, this paper discusses the relationship between the use of code mixing in the Indonesian people's everyday life with the nation‟s identity as a country that is bhineka (mentioned as its official national motto) or diversed. Instead of being not nationalist, the practice of code mixing by the Indonesian people is actually a manifestation of the identity of the Indonesian people as a diverse society. The code mix that occurs in the daily life of the community is proof that Indonesian people can understand each other and communicate well in a very complex diversity